Bleomycin sclerotherapy in lymphangiomas of the head and neck region: a prospective study. Issue 5 (May 2021) - Tiwari, P.; Pandey, V.; Bera, R.N.; Sharma, S.P.; Chauhan, N.
Abstract: Intralesional sclerotherapy for lymphatic malformations (LMs) has become a modality of choice because of the high morbidity and recurrence rates with surgical excision. Traditionally, the macrocystic variant has shown good results with sclerotherapy. This prospective study was performed to evaluate the role of bleomycin sclerotherapy in the management of different radiological variants of LM. A total of 142 patients were included in this study. The lesions were classified as macrocystic, microcystic, or mixed LMs on the basis of ultrasonography. All patients were managed by intralesional injection of bleomycin and were recalled after 4 weeks for evaluation. Colour photographs of the patients were taken before the onset of treatment and at each monthly visit, and were utilized to assess the response. Following the second, third, and fourth doses, the response was better in patients with the macrocystic variant than in those with the other two variants. However, after the completion of six doses, 80.3% of patients with the macrocystic variant, 67.4% with the microcystic variant, and 71.4% with the mixed type had a complete response. There was no difference in the overall response between the three types ( P  = 0.28). Oedema, erythema, and local induration with fever were the most common adverse effects and were more common in younger children.